Crystalline Porous Organic Salts: Crystalline Porous Organic Salts: From Micropore to Hierarchical Pores (Adv. Mater. 44/2020). Issue 44 (3rd November 2020) - Yu, Shen; Xing, Guo‐Long; Chen, Li‐Hua; Ben, Teng; Su, Bao‐Lian
Abstract : Crystalline porous organic salts (CPOSs) with a microporous polarized channel system offer a large array of fascinating properties including proton conductivity, CO2 diffusion, colossal negative linear compressibility, and molecular rotors, as reviewed by Li‐Hua Chen, Teng Ben, Bao‐Lian Su, and co‐workers in article number 2003270 . The introduction of hierarchical porosity to CPOSs leads to new properties and a new upsurge in research.